Arthroscopic Tibiotalar Arthrodesis versus Open Arthrodesis with Anterior Locking Plate: A Retrospective Case Series. Issue 4 (22nd October 2020) - Jong, Benjamin Y.; Femino, John E.; Netto, Cesar de Cesar; Phisitkul, Phinit
Category: Ankle; Ankle Arthritis; Arthroscopy Introduction/Purpose: Tibiotalar arthrodesis is a common procedure for the treatment of ankle arthritis. Arthroscopic arthrodesis with screw fixation has become increasingly popular with reported shorter hospital stays, shorter time to fusion, and equivalent patient reported outcomes to open arthrodesis with screw fixation. However, there is limited research comparing arthroscopic arthrodesis to open arthrodesis with a modern anterior locking plate. The aim of this study was to determine if the use of a modern anterior locking plate in primary ankle arthrodesis would have a similar time to fusion versus arthroscopic arthrodesis with screw fixation. Methods: We performed a retrospective case review of primary ankle arthrodesis cases from 2009 to 2018 that utilized either an open approach with an anterior locking plate or an arthroscopic approach with screw fixation. All open cases were performed by a single surgeon using an anterior locking plate; all arthroscopic cases were performed by another surgeon using cannulated screw fixation. Post-operative protocol was similar for both patient groups, with at least 6 weeks of casting and protected weight- bearing followed by a transition to removable cast-boot and progressive weight-bearing. Exclusion criteria included combined tibiotalar/subtalar arthrodesis, hindfoot arthrodesis, cases where infection was suspected pre-operatively, and revision arthrodesis for any reason (IE, infection, failed total ankle arthroplasty, prior nonunion). Time to fusion was based on evaluation of post- operative radiographs performed at six and ten weeks. Results: 28 open and 25 arthroscopic arthrodesis cases met inclusion criteria. The fusion rate at six weeks was 82.1% (open) versus 72% (arthroscopic). At ten weeks the fusion rate was 100% (open) versus 91% (arthroscopic). 4/28 open arthrodesis cases experienced continued pain versus 8/25 arthroscopic. For the open procedure, one patient required reoperation for skin grafting away from the incision due to a poor-fitting workboot. Two patients had removal of painful hardware; one of these patients required a second reoperation for symptomatic neuroma resection. For arthroscopic cases, two patients had removal of hardware and one patient had an elective below-knee amputation for intractable pain. Average patient age was 53.3 years (open) versus 48.4 (arthroscopic). Average length of hospital admission was 2.3 days (open) versus 0.9 (arthroscopic). Conclusion: Open tibiotalar arthrodesis with a modern anterior locking plate resulted in faster time to radiographic fusion and a lower incidence of continued pain compared to arthroscopic arthrodesis in this study. The faster time to fusion may be due to the superior biomechanical stability of a locking construct. Arthroscopic arthrodesis resulted in shorter hospital admissions, and neither group had any incision-related complications. In this case series, open and arthroscopic fusion had comparable outcomes.